Interactions of thought and language in Old English poetry - Clemoes, Peter (Cambridge University Press, 1995)
Peter Clemoes brings a lifetime's close study of Anglo-Saxon texts to this appreciation of Old English poetry, with an alternative interpretation which relates the poetry to both the entire Anglo-Saxon way of thinking and the structures of its society. Clemoes proposes a dynamic principle of Old English poetry, very different from the common notion of formulas slotted into poems for stylistic variation. In extended discussions of particular poems and images as well as of changes in language, he shows how the poetic medium became a vehicle for increasing transformation to Christian literacy and to that religion's conceptions of the natural world, morality, and individuality. Carefully thought out and elegantly written, this book is also accessible to students: its numerous quotations are accompanied by modern English translations.
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Altenglisch; Lyrik